THE INFLUENCE OF THE NATURAL PRODUCT PRACTICUM ON DECISION MAKING SKILLS - Hakim, Aliefman; Jufri, Abdul Wahab; Jamaluddin, Jamaluddin; Septiani, Devi Ayu; Ningsih, Baiq Nila Sari; Supriadi, Supriadi (Universitas Negeri Surabaya, 2022)
The study of secondary metabolites is the core of Natural Product Chemistry. The process of isolating secondary metabolites from Sasambo plants, which are medicinal plants used by indigenous tribes in West Nusa Tenggara province, Indonesia, has the potential to be integrated into the Natural Product Chemistry Practicum. Students learn how to extract, fractionate, purify, and identify the structure of secondary metabolites through Natural Product Chemistry Practicum. With various alternative actions related to the process of isolating secondary metabolites, these laboratory exercises can be utilized to help students improve their decision-making skills. This study aims to investigate the impact of Natural Product Chemistry Practicum Based on Medicinal Plants Sasambo (NPP-MPS) on students' decision-making skills. This is quasi-experimental research with nonequivalent control group pretest-posttest research design. The participants are 63 students who enrolled in 6th semester students of the chemistry education department at one of the state universities in West Nusa Tenggara, Indonesia, for the 2019/2020 academic year, which were divided into experimental and the control classes. The findings show that the NPP-MPS does positively influences students' decision-making skills.